2014
DOI: 10.1371/journal.pone.0086326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying Degrees of Intermittent Hypoxia on Proinflammatory Cytokines and Adipokines in Rats and 3T3-L1 Adipocytes

Abstract: ObjectivesIntermittent hypoxia (IH), resulted from recurring episodes of upper airway obstruction, is the hallmark feature and the most important pathophysiologic pathway of obstructive sleep apnea (OSA). IH is believed to be the most important factor causing systemic inflammation. Studies suggest that insulin resistance (IR) is positively associated with OSA. In this study, we hypothesized that the recurrence of IH might result in cellular and systemic inflammation, which was manifested through the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 64 publications
5
58
0
Order By: Relevance
“…It is known that as a part of adaptive response to hypoxia, there is upregulated expression of several genes encoding glycolytic enzymes. 27 However, to our best knowledge, an IHT-induced change in mRNA expression of these genes has not been reported prior to our current study. Our present results showed that whereas no significant difference in baseline expression of the examined genes between prediabetes and healthy subjects, the changes in HIF-1a-regulated gene expression in response to IHT was subsequent to those of HIF-1a mRNA in the healthy group and the maximum response was observed one month after the end of IHT (Figure 1(b) to (d)).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It is known that as a part of adaptive response to hypoxia, there is upregulated expression of several genes encoding glycolytic enzymes. 27 However, to our best knowledge, an IHT-induced change in mRNA expression of these genes has not been reported prior to our current study. Our present results showed that whereas no significant difference in baseline expression of the examined genes between prediabetes and healthy subjects, the changes in HIF-1a-regulated gene expression in response to IHT was subsequent to those of HIF-1a mRNA in the healthy group and the maximum response was observed one month after the end of IHT (Figure 1(b) to (d)).…”
Section: Discussionmentioning
confidence: 49%
“…24,25 GLUT-1 is upregulated under hypoxia, and its activity depends of the severity of hypoxic impact. 26,27 Another HIF-1a target gene important for glucose homeostasis is insulin receptor (INSR). Insulin exerts its physiological effects through this member of tyrosine kinase family of transmembrane signaling proteins encoded by a single gene INSR.…”
Section: Introductionmentioning
confidence: 99%
“…RAECs grown in culture plates were placed in Plexiglas exposure chamber and exposed to IH conditions for 5 h. Consequently, RAECs were cocultured with lymphocytes with IH or air for another 4 h at the ratio of lymphocytes/endothelial cells 10:1. The hypoxia exposure protocol for cell incubation was similar with that reported in our previous study [16].…”
Section: Intermittent Hypoxia Treatmentmentioning
confidence: 61%
“…All rats were randomly allocated to six groups (n = 5 each): A. normoxia control group (NC); B. chloroquine treatment group (CQ), intraperitoneal injection of chloroquine (60 mg/kg/day); C. rapamycin treatment group (RA), intraperitoneal injection of rapamycin (0.5 mg/kg/day); D. IH group (IH); E. IH and chloroquine treatment group (IH+CQ), intraperitoneal injection of chloroquine (60 mg/kg/day) prior to IH exposure; and F. IH and rapamycin treatment group (IH+RA), intraperitoneal injection of rapamycin (0.5 mg/kg/day) prior to IH exposure. The IH animal model was established according to the procedures described by He et al [17].. Briefly, model rats were exposed to IH for 6 weeks, 8 h/day (9 AM to 5 PM) in a specialized Plexiglas chamber.…”
Section: Animals and Ih Exposurementioning
confidence: 99%